2008
DOI: 10.1002/app.29043
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic properties of aqueous dextran solutions

Abstract: The hydrodynamic performance of aqueous dextran solutions, including the rheological and thixotropic properties, were investigated. Three kinds of dextrans with different molecular weights were employed to examine the effects of the molecular weight, concentration, temperature, and so forth on the hydrodynamic properties of aqueous dextran solutions. The results showed that an aqueous solution of a dextran with a high molecular weight of 5.223 Â 10 5 at a high concentration of 30 wt % had pseudoplastic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Video S1 shows the behavior of the viscous stock solutions of dextran and PEO. Consistent with other reports of the viscoelastic behavior of dextrans of various molecular weights and concentrations, , as well as our previous work, the solution of 50 wt % dextran behaved as a Newtonian fluid, although some studies have observed modest shear-thinning behavior for high molecular weight dextrans of 30 wt % or above attributed to presence of branches within the dextran chains . In contrast, PEO behaved as a non-Newtonian shear-thinning fluid at all concentrations above those sufficient for entanglement to occur, which was consistent with previous reports of the rheology of aqueous solutions of PEO. , Contrary to dextran solutions, for which we previously showed that the time scale for fiber formation was purely controlled by the entanglement dynamics, this implies that the time scale for fiber formation from the PEO solution is controlled by the entanglement dynamics and by a shear strain rate-dependent thinning process such as the elastocapillary regime described by Dinic and Sharma …”
Section: Results and Discussionsupporting
confidence: 92%
“…Video S1 shows the behavior of the viscous stock solutions of dextran and PEO. Consistent with other reports of the viscoelastic behavior of dextrans of various molecular weights and concentrations, , as well as our previous work, the solution of 50 wt % dextran behaved as a Newtonian fluid, although some studies have observed modest shear-thinning behavior for high molecular weight dextrans of 30 wt % or above attributed to presence of branches within the dextran chains . In contrast, PEO behaved as a non-Newtonian shear-thinning fluid at all concentrations above those sufficient for entanglement to occur, which was consistent with previous reports of the rheology of aqueous solutions of PEO. , Contrary to dextran solutions, for which we previously showed that the time scale for fiber formation was purely controlled by the entanglement dynamics, this implies that the time scale for fiber formation from the PEO solution is controlled by the entanglement dynamics and by a shear strain rate-dependent thinning process such as the elastocapillary regime described by Dinic and Sharma …”
Section: Results and Discussionsupporting
confidence: 92%
“…To characterize non-spherical samples, we prepared a highly viscous medium composed of aqueous dextran (35% by weight) in 3.00 M MnCl 2 ; for this solution, we measured  m = 1.385 g/cm 3 . This highly viscous liquid (viscosity ~10 Pa•s, 18 or approximately that of honey) enabled us to use viscous drag to "pick up" the sample and rotate it with the container, about the z-axis. Figure 2 shows a schematic of this procedure: after rotating the container by 180 and then stopping, the sample fell gradually back to the bottom surface of the container.…”
Section: Experimental Expanding the Range Of Levitated Densities By Rmentioning
confidence: 99%
“…For powders of glass and aluminum, we used a solution with no added dextran. For tin and copper powders, we added 10% (by weight) dextran (viscosity ~ 0.2 Pa•s) 18 . For gold powder, we added 35% dextran (by weight).…”
Section: Experimental Expanding the Range Of Levitated Densities By Rmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the average degree of polymerization of poly[(1,6-bis(N-methylimidazolium)hexa-2,4-diyne)dibromide] lies between 15 and 35 with a polydispersity index of about 1.2 and a weight average hydrodynamic radius of 1.77 nm. Higher concentrations in dextran (up to 30% with a lower molar mass polymer for limiting the increase in viscosity) 62 could increase the resolution of the oligomeric polydiacetylene separation. Indeed, it has been reported in a previous work 63 that no separation of DNA oligomers could be achieved using a 10% dextran solution while excellent baseline separation was obtained with a 30% dextran concentration.…”
Section: Discussionmentioning
confidence: 99%